Characteristics of and factors associated with dengue vector breeding sites in the City of Colombo, Sri Lanka - Louis, Valérie R.; Montenegro Quiñonez, Carlos Alberto; Tozan, Yeşim; Wilder-Smith, Annelies (Pathogens and global health, 2016)
Introduction: Dengue has emerged as a major public health problem in Sri Lanka. Vector control at community level is a frequent and widespread strategy for dengue control. The aim of the study was to assess Aedes mosquito breeding sites and the prevention practices of community members in a heavily urbanized part of Colombo. Methods: A cross-sectional entomological survey was conducted from April to June 2013 in 1469 premises located in a subdistrict of the City of Colombo. Types of breeding sites and, where found, their infestation with larvae or pupae were recorded. Furthermore, a questionnaire was administered to the occupants of these premises to record current practices of dengue vector control. Results: The surveyed premises consisted of 1341 residential premises and 110 non-residential premises (11 schools, 99 work or public sites), 5 open lands, and 13 non-specified. In these 1469 premises, 15447 potential breeding sites suitable to host larvae of pupae were found; of these sites18.0% contained water. Among the 2775 potential breeding sites that contained water, 452 (16.3%) were positive for larvae and/or pupae. Schools were associated with the proportionally highest number of breeding sites; 85 out of 133 (63.9%) breeding sites were positive for larvae and/or pupae in schools compared with 338 out of 2288 (14.8%) in residential premises. The odds ratio (OR) for schools and work or public sites for being infested with larvae and/or pupae was 2.77 (95% CI 1.58, 4.86), when compared to residential premises. Occupants of 80.8% of the residential premises, 54.5% of the schools and 67.7% of the work or public sites reported using preventive measures. The main prevention practices were coverage of containers and elimination of mosquito breeding places. Occupants of residential premises were much more likely to practice preventive measures than were those of non-residential premises (OR 2.23; 1.49, 3.36). Conclusion: Schools and working sites were associated with the highest numbers of breeding sites and lacked preventive measures for vector control. In addition to pursuing vector control measures at residential level, public health strategies should be expanded in schools and work places.